2005
DOI: 10.1179/174328205x40536
|View full text |Cite
|
Sign up to set email alerts
|

Hardening enhances photoprotection in the mossAtrichum androgynumduring rehydration by increasing fast- rather than slow-relaxing quenching

Abstract: Chlorophyll fluorescence was used to study the effect of a hardening treatment on aspects of desiccation tolerance in the moss Atrichum androgynum. Mosses were hardened by reducing the relative water content of apical stem segments to 0.5 for 3 days, followed by storing the material fully hydrated for 1 day. Desiccation tolerance was assessed by storing plants over silica gel for 16 h, and then monitoring the recovery of photosystem II during rehydration. Hardening decreased the efficiency of photosystem II be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…; Beckett et al . , ; Cruz de Carvalho et al . ; Marschall & Borbély ), the mechanism of inducible DT in Sphagnum species and its impact on peatland ecology have not been considered so far.…”
Section: Discussionmentioning
confidence: 99%
“…; Beckett et al . , ; Cruz de Carvalho et al . ; Marschall & Borbély ), the mechanism of inducible DT in Sphagnum species and its impact on peatland ecology have not been considered so far.…”
Section: Discussionmentioning
confidence: 99%
“…For bryophytes, plenty of studies has demonstrated that experienced desiccation can make them adapt to desiccation stress better (Beckett, 1999;Beckett, Marschall, & Laufer, 2005;Bopp & Werner, 1993;Dilks & Proctor, 1976;Schonbeck & Bewley, 1981a, 1981bWerner, Ros Espín, Bopp, & Atzorn, 1991); however, this stress imprinting tends to wear off with the extension of the recovery time, and slower desiccation rates produce longer imprinting times (Brinda, Stark, Clark, & Greenwood, 2016). For naturally growing mosses in the field, water between dense individuals generally leads to relatively slow desiccation rates and the intervals between dry events varied.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum fluorescence (Fm) of dark-adapted leaf was obtained after a brief saturating flash (approximately 8 s). Further details of the fluorescence parameters measured were as outlined previously (Genty et al 1989;Beckett et al 2005). In the current study, four actinic lights: 264, 488, 800 and 1,200 lmol PAR m -2 s -1 were switched on at a regular interval (5 min).…”
Section: Photosynthetic Pigment Content and Chlorophyll Fluorescence mentioning
confidence: 99%
“…The phytochemical quenching parameters evaluated were maximum quantum yield of PSII (Fv/Fm), actual quantum yield of PSII (/ PSII ) and photochemical quenching (qP). In addition, non-photochemical quenching (NPQ) and relative electron transport rate (ETR) at the four light intensities were calculated as outlined by Beckett et al (2005). According to Zribi et al (2009), these aforementioned parameters are indicator of photosynthetic disturbance in tomato under salt stress.…”
Section: Photosynthetic Pigment Content and Chlorophyll Fluorescence mentioning
confidence: 99%